The Application of National Criminal Law in the Settlement of Criminal Cases in the Baduy Customary Law Community - Latu, Mery Anthonia Nasta (International Journal of Education, Information Technology, and Others, 2024)
Indonesia is a country of law, but on the other hand, Indonesia is also rich in diversity of customs. In this case, the existence of national law is related to the existence of customary law, especially related to criminal cases. The scientific work of this journal aims to explain the application of national criminal law associated with the customary law of the Baduy community, especially in terms of resolving criminal cases. The research method used in this journal is qualitative descriptive, where the explanations listed are sourced from various literature related to the material of this journal. The result obtained from the explanation stated in this journal is that in the settlement of criminal cases, the indigenous Baduy prioritize mediation at the family level first, which then if it cannot be resolved at the family level, it will rise to a higher level by involving interested indigenous leaders. In criminal cases, the indigenous people of Baduy also know several principles in the national criminal law, as well as forms of criminal acts as embraced in the national criminal law.